PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING TERHADAP PERILAKU AGRESI VERBAL PADA SISWA DI SMAN 4 KOTA JAMBI - Rizka Fitriani; Muhammad Ferdiansyah; Muhammad Alridho Lubis (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Verbal aggression behavior among students is a common issue in schools, including at SMAN 4 Kota Jambi. If left unaddressed, this behavior can damage relationships between students. To reduce verbal aggression, group counseling services using the Role Playing technique were implemented. This study aims to determine: (1) the level of verbal aggression behavior in students before the intervention, (2) the level of verbal aggression behavior in students after the intervention, and (3) the impact of group counseling services using the Role Playing technique on students' verbal aggression behavior at SMAN 4 Kota Jambi. This quantitative study employs an experimental method with a pre-experimental one-group pretest-posttest design. The population consists of students from classes XI.F10 and XI.F12 at SMAN 4 Kota Jambi, with a sample of 10 students selected using purposive sampling based on recommendations from the school counselor. Data were collected using a verbal aggression behavior questionnaire with 35 items. Data analysis was conducted using KIN (Kontiunum Internal Normatif) and T-test. The pretest results showed an average verbal aggression behavior score of 114.1, categorized as high. After the intervention, the posttest average score dropped to 74.2, categorized as moderate. The T-test results showed a T-value of 7.603, which is greater than the T-table value of 2.228, with a Sig. (2-tailed) value of 0.000, indicating a significant difference between pretest and posttest scores. In conclusion, group counseling services using the Role Playing technique significantly impact reducing verbal aggression behavior among students.